Rethinking play as pedagogy - Alcock, Sophie 1953-; Stobbs, Nicola (Thinking about pedagogy in early childhood education, 2019)
The conceptualisation and practice of play is considered core to early childhood pedagogy. In this essential text, contributors from a range of countries and cultures explore how play might be defined, encouraged and interpreted in early childhood settings and practice. Rethinking Play as Pedagogy provides a fresh perspective of play as a purposeful pedagogy offering multi-layered opportunities for learning and development. Written to provoke group discussion and extend thinking, opportunities for international comparison, points for reflection and editorial provocations, this volume will help students engage critically with a variety of understandings of play, and diverse approaches to harnessing children's natural propensity to play. Considering the role of the learning environment, the practitioner, the wider community, and policy, chapters are divided into four key sections which reflect major influences on practice and pedagogy: Being alongside children Those who educate Embedding families and communities Working with systems Offering in-depth discussion of diverse perceptions, potentials and practicalities of early childhood play, this text will enhance understanding, support self-directed learning, and provoke and transform thinking at both graduate and postgraduate levels, particularly in the field of early childhood education and care, for students, educators, integrated service providers and policy makers